2014
DOI: 10.1038/bmt.2014.71
|View full text |Cite
|
Sign up to set email alerts
|

The skinny on obesity and plasma cell myeloma: a review of the literature

Abstract: Despite tremendous advances in treatments for myeloma in the past decade, the disease remains incurable in the majority of patients. Here, we review recent data demonstrating an association between obesity and increased risk of myeloma development. This may be due to the pro-inflammatory cytokine profile caused by obesity. Currently, there are no screening or prevention strategies for myeloma, but we propose that obesity-associated inflammatory pathways, or obesity itself, may be amenable to intervention, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 107 publications
0
42
0
Order By: Relevance
“…2 In addition to being a potential risk factor for MM, some, but not all, studies have suggested an association between BMI and prognosis. 1, 3 A recent study has suggested the relationship between BMI and MM may be through reduced levels of plasma adiponectin, the inflammatory mediator secreted by adipocytes.…”
mentioning
confidence: 99%
“…2 In addition to being a potential risk factor for MM, some, but not all, studies have suggested an association between BMI and prognosis. 1, 3 A recent study has suggested the relationship between BMI and MM may be through reduced levels of plasma adiponectin, the inflammatory mediator secreted by adipocytes.…”
mentioning
confidence: 99%
“…Increasing evidence now indicates a link between obesity and myeloma incidence [152]. In fact, leptin levels were found to be increased in the serum of non-obese myeloma patients, with concentration correlating with disease progression [153].…”
Section: Adipocytesmentioning
confidence: 99%
“…Several of the cytokines (eg, leptin and interleukin-6), increased in obese subjects, can act directly on myeloma and myeloid cells through ligand-receptor interactions regulating proliferative rate and or apoptosis. 9,29,31,32 Clonal hematopoiesis of indeterminate potential is now an accepted concept. [37][38][39] Individuals with such clones have an increased likelihood of progression to an overt myeloid malignancy, usually myelodysplasia or acute myelogenous leukemia.…”
mentioning
confidence: 99%
“…The evidence for an increased risk of myeloma as a result of overweight and obesity is compelling. [3][4][5][6][7][8][9][10][11] Of special interest is whether the precursor of myeloma, essential monoclonal gammopathy (also known as monoclonal gammopathy of unknown significance), has an increased risk of occurrence in obese patients. An initial study indicated that it did, 11 whereas a recent study has challenged that finding.…”
mentioning
confidence: 99%
See 1 more Smart Citation